Studi Kompleks Assosiasi Pb(II) Menggunakan KI dan Methylene Blue - Fadilla Yuri Merti; Edi Nasra; Desy Kurniawati (Jurnal Periodic Jurusan Kimia UNP, 2023)
Research has been carried out on the study of the Pb(II) association complex using KI and methylene blue. This study aims to find the optimum conditions for the Pb(II) association complex such as optimum time, Iodidae concentration, pH, and methylene blue concentration. The measurement methods used are UV-Vis spectrophotometry and AAS (Atomic Absorption Spectrophotometer). Pb(II) is reacted with excess Iodidae to form an anion complex (PbI42-). The anion complex formed is then reacted with a methylene blue (MB+) cation complex to form an association complex [MB]2[PbI4]. From the results of the study, it was found that the optimum conditions for the formation of anion complexes (PbI42-) at 2 hours, a concentration of 0.4 M with an absorbance of 0.1069 A at anion wavelength of 266 nm. While the optimum conditions for the association complex [MB]2[PbI4] occurred at a wavelength of 665 nm with an absorbance of 0.6119 A, pH 3 with an absorbance of 0.9675 A and a concentration of 0.0012 % methylene blue with an absorbance of 0.1266 A. The association complex The resulting product was contacted with Pb(NO3)2 at a concentration of 0.01 ppm and was successfully concentrated by obtaining a concentration of 0.6387 ppm and an absorbance value of 0.0092 A. So that a concentration factor of 63.87 times was obtained.